Pengaruh Hubungan Personal Terhadap Kepuasan Kerja CV Permata Karya Jaya Surabaya - Lia Ika Prawati; Nur Aini Anisa (FEB Universitas Maritim Semarang, 2023)
Prawati Ika Lia 1961201047 Sekolah Tinggi Ilmu Ekonomi Pemuda Advisor Anisa Nur Aini S.PD,. M.P.D The Impact of Personal Relationships on Job Satisfaction at CV Permata Jaya. This research was conducted to see the impact of personal relationships on job satisfaction at Cv Permata Karya Jaya. Researchers use quantitative techniques. Quantitative research, the sampling technique in this study is a saturated sample, all employees 64 workers from all departments as a sample. The results of the study show that personal relationships (X) have a significant effect on job satisfaction (Y). In this case it proves that one way to increase employee satisfaction is by providing good interpersonal relationships. With good relationships and interactions, job satisfaction is created.